Simball Box for Laparoscopic Training With Advanced 4D Motion Analysis of Skills. (June 2016) - Hagelsteen, Kristine; Sevonius, Dan; Bergenfelz, Anders; Ekelund, Mikael
Background . Laparoscopic skills training and evaluation outside the operating room is important for all surgeons learning new skills. To study feasibility, a video box trainer tracking 4-dimensional (4D) metrics was evaluated as a laparoscopic training tool. Method . Simball Box is a video box trainer with authentic surgical instruments and camera with video recording, equipped with 4D motion analysis registered through trocars using machine vision technology. Residents attending a 3-day laparoscopy course were evaluated performing a laparoscopic surgical knot at start, middle, and end. Metrics were obtained. Feedback data were presented in reference to expert/tutorial performance. Results . Ten right-handed residents were included. Median time (range) to finish the task was 359 (253-418), 129 (95-166), and 95 (52-156) seconds; 655%, 236%, and 174% of tutorial performance, with significance pre-/midcourse ( P < .0001), pre-/postcourse ( P < .0001), and mid-/postcourse ( P = .0050). Combined median total instrument motion decreased pre-/midcourse from 1208 (845-1751) to 522 cm (411-810 cm); P = .042 to 405 cm (246-864 cm) postcourse; pre-/postcourse P < .0001; 673%, 291%, 225% of tutorial performance. Total angular distance in radians (range) was 150 (87-251), 65 (42-116), and 50 (33-136) with significance pre-/midcourse ( P = .022) and pre-/postcourse ( P = .0002). Right-handed average speed (cm/s) increased: 1.94 (1.11-2.27) pre-, 2.39 (1.56-2.83) mid-, 2.60 (1.67-3.19) postcourse with significance pre-/midcourse ( P = .022) and pre-/postcourse ( P = .002). Average acceleration (mm/s 2 ) and motion smoothness (µm/s 3 ) failed to show any difference. Conclusion . For laparoscopic training and as a promising evaluation device, Simball Box obtained metrics mirroring progression well.